2021
DOI: 10.1111/jtxs.12638
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental characteristics from extensional rheology and tribology of polysaccharide solutions

Abstract: Instrumental characteristics from extensional rheology and tribology for aqueous xanthan gum (XG) and locust bean gum (LBG) solutions were studied in the presence or absence of simulated saliva. Extensional viscosity was calculated from the filament shrinkage behavior using a capillary breakup extensional rheometer, whereas the friction coefficient was measured using a set‐up consisting of polydimethylsiloxane substrate and a glass ball bearing on a rotational rheometer. Increase in extensional viscosity was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…It was found that η e for both XG and LBG decreased and then increased with increasing Hencky strain but the increase of η e was more noticeable for LBG, which might be explained by the difference in chain stiffness of XG and LBG 270) . Since LBG is more flexible than XG the coil-stretch transition occurs more clearly than in XG.…”
Section: Cohesivenessmentioning
confidence: 91%
See 3 more Smart Citations
“…It was found that η e for both XG and LBG decreased and then increased with increasing Hencky strain but the increase of η e was more noticeable for LBG, which might be explained by the difference in chain stiffness of XG and LBG 270) . Since LBG is more flexible than XG the coil-stretch transition occurs more clearly than in XG.…”
Section: Cohesivenessmentioning
confidence: 91%
“…In relation to this, "structured fluid" having the yield stress leads to the formation of one coherent bolus that is then swallowed in one go, presenting a rheological nature for swallowing ease. Funami and Nakauma 270) reported that perceived sliminess had the highest correlation with the friction coefficient at the point E in the Stribeck curve, which corresponds to entrainment speed of 6 × 10 −3 m/s. According to a flow simulation study 271) the bolus flow for non-Newtonian fluids (xanthan gum and guar gum used in Nishinari et al 199) with the viscosity more than 10 times higher than the solutions used 270) was ~ 0.3 m/s at the palate, 0.3 ~ 0.5 m/s at the pharynx, and 0.1 ~ 0.4 m/s at the larynx/esophagus, depending on feeding volume from 5 to 10 ml.…”
Section: Tribological Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In organizing this special issue, our main consideration has been on the fundamental principles and feasible techniques of texture modification for adult dysphagia. For this purpose, a number of leading scientists have been approached for a contribution in topics including the effect of bolus rheology of texture-modified foods on the degree of modification (Stading, 2021a); relationship between masticatory variables and bolus characteristics of meat with different textures (Pematilleke, Kaur, Adhikari, & Torley, 2021); textural properties and muscle activities during mastication of normal and ultrasonically softened sticky rice (Wattanapan, Saengnil, Niamnuy, Paphangkorakit, & Devahastin, 2021); extensional rheology and tribology of polysaccharide solution (Funami & Nakauma, 2021); the physical properties of texture-modified foods (Stading, 2021b); the effect of the rheological properties of thickened fluids on the in vitro swallowing of solid oral dosage forms (Lavoisier, Shreeram, Jedwab, & Ramaioli, 2021); and microwave treatment to modify textural properties of high-protein gel applicable as dysphagia food (Pure, Yarmand, Farhoodi, & Adedeji, 2021).…”
mentioning
confidence: 99%